Development of an Adaptive Gamification Learning Model Based on Artificial Intelligence to Create an Interactive, Personalized, and Enjoyable Learning Environment - Siti Lufniyah; Hilmi Mizani (Yayasan Pendidikan Tanggui Baimbaian, 2026)
The rapid advancement of digital technology and Artificial Intelligence (AI) has transformed education, requiring innovative approaches that enhance learner engagement and experiences. Although gamification effectively increases motivation and participation, most implementations remain static and fail to address individual learning needs. This study proposes an Adaptive AI-Based Gamification Learning Model that integrates dynamic challenges, personalized rewards, intelligent feedback, and real-time learning analytics. Using a conceptual research approach and literature review, the study develops a framework combining gamification, adaptive learning, and AI-driven personalization. The findings suggest that AI-enhanced gamification can improve motivation, engagement, self-regulated learning, and academic outcomes through continuous adaptation to learners’ abilities, preferences, and progress. The proposed framework contributes to educational technology research by offering a learner-centered model for more effective and adaptive instruction in the digital era.